Analysis of cultural ecosystem services and heritage tourism based on social media: Virtual learning on tourism information management - Tim Chen; Dogrua Makara; Courtne Sean; Suessc McGinleya; Johnnycy Cheng (African Journal of Hospitality, Tourism and Leisure, 2020)
Due to the far-reaching nature of the Internet and the rapid development of global information. Tourists and learners of different time and space can participate in sightseeing activities through the Internet, resulting in changes in sightseeing styles, which not only change the presentation of knowledge, but also change the way of learning information exchange, and the sightseeing environment also. Therefore, the real environment of the traditional classroom is extended to the networked virtual world of learning. As far as users are concerned, the biggest difference in sightseeing websites lies in the learning mode provided by the entire network sightseeing. However, it can be roughly divided into two different types: (1) established by the enterprise organization and (2) required to be charged. Courses and websites can be established by school units. Online tourism is a new type of education derived from the digital revolution and 4IR. The vigorous development in the country is also an important way for the government to achieve the goals of "lifelong learning" and its "knowledge economy" policy. The industry believes that the most important projects it must be involved in are: (a) establishing its own leading position in online tourism expertise (b) using learner feedback as a basis for improving network tourism (c) continuing research and development to expand the capabilities of the network sightseeing platform; scholars believe that the most Important projects are: (a) the establishment of a school network sightseeing unit (b) to improve the interaction between the tourism network and the visitors (c) to provide a variety of course contents. However, in all the problems and difficulties faced, the industry believes that the most important difficulty is to make the public see the digital changes as popular events and accept the way to identify online tourism; scholars believe that the related technology of network tourism needs to be strengthened.